Isolation, Characterization and Antibacterial Activity of Endophytic Fungi from Marrubium vulgare L. - Abderrahim Benslama; Warda Nouiri (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this work is the isolation, identification and evaluation of the antibacterial activity of endophytic fungi from the Algerian medicinal plant Marrubium vulgare L. The isolation of endophytic fungi is carried out by the method of sterilization of surface to eliminate epiphytes then incubation of the fragments treated according to a precise protocol. The identification of the grown isolates allowed us to obtain three fungal strains belonging to three genera: Fusarium, Alternaria and Chaetomium, which are generally of the Deuteromycete phylum. The antibacterial capacity of the fungi was tested against five human pathogenic bacteruim using the agar-fungi disk diffusion method. With an inhibition zone (IZ) spanning from 7.5 to 25 mm, all isolated fungal strains showed antibacterial activity against at least one of the bacteria tested.. However, Fusarium sp has the highest antibacterial activity with an IZ of 19 and 24 mm against S. aureus and B. subtilis, respectively. Finally, our results clearly confirm that the medicinal plant M. vulgare L. presents a reservoir of endophytic fungi, which can be used in various fields, especially pharmaceutical fields.